CD47 limits antibody dependent phagocytosis against non-malignant B cells. (May 2017) - Gallagher, Sandra; Turman, Sean; Lekstrom, Kristen; Wilson, Susan; Herbst, Ronald; Wang, Yue
Highlights: Plasma cells have highest expression of CD47 among murine B cell subsets. CD47 limits anti-CD19 dependent phagocytosis against non-malignant B cells. Blocking CD47 function with a F(ab')2 anti-CD47 antibody can enhance B cell depletion Abstract: Recent studies have demonstrated the importance of CD47 in protecting malignant B cells from antibody dependent cellular phagocytosis (ADCP). Combined treatment of anti-CD47 and −CD20 antibodies synergistically augment elimination of tumor B cells in xenograft mouse models. This has led to the development of novel reagents that can potentially enhance killing of malignant B cells in patients. B cell depleting therapy is also a promising treatment for autoimmune patients. In the current study, we aimed to investigate whether or not CD47 protects non-malignant B cells from ADCP. We show that CD47 is expressed on all B cells in mice, with the highest level on plasma cells in bone marrow and spleen. Although its expression is dispensable for B cell development in mice, CD47 on B cells limits antibody mediated phagocytosis. B cell depletion following in vivo anti-CD19 treatment is more efficient in CD47-/- mice than in wild type mice. In vitro, both naïve and activated B cells from CD47-/- mice are more sensitive to ADCP than wild type B cells. Lastly, we show in an ADCP assay that blocking CD47 can enhance anti-CD19 antibody mediated phagocytosis of wild type B cells. These results suggest that in addition to its already demonstrated benefit in cancer, targeting CD47 may be used as an adjunct in combination with B cell depletion antibodies for treatment of autoimmune diseases.